The effects of Nigella sativa oil administration on some physiological and histological values of reproductive aspects of rats: Farooq T Juma Hayfaa M A Abdulrahman - Juma, Farooq T. (The Iraqi Journal of Veterinary Medicine, 2011)
The goal of this study to investigate the effects of Nigella sativa (Ns) oil on reproductive values, some hematological parameters serum biochemical characteristics, some sexual hormones concentration and histological changes of treated and normal male reproductive organs. The experiment (1) dealt with 20 males and 20 female rats at 21 days of age, 10 rats of each sex were giving orally Ns oil at the rate of 1ml/kg/day for 30 days and the others left as a control group. Insignificant changes were occurred in hematological parameters except the white blood cells (WBCs), were significantly increased in treated groups (P<0.05). The treated groups showed significant increases in total protein and significant decreases in total cholesterol liver enzymes markedly increased in treated rats Significant increases in the levels of LH, FSH and testosterone for males and LH, FSH, estrogen and progesterone for females were recorded. The experiment (2) dealt with effects of Ns oil on 20 adult males and 20 adult female rats that were given same dose of Ns oil for 30 days. There were significant increase in litter size and weight of rats born in treated groups. The experiment (3) dealt with the effects of Ns oil on castrated males fifteen adult rats were divided equally into 3 groups, two groups were castrated while, the third group was left as a control group; one castrated group was treated with same dose of Ns oil for 30 days, there were significant increases in serum testosterone concentration and weight of accessory glands in treated group. Histological changes in the accessory glands of treated groups were evident.In conclusion, the administration of 1ml/kg/day of Ns oil stimulated the secretion of sexual hormones that led to improve protein synthesis of hepatic enzymes, white blood cells count and decrease the serum cholesterol concentration in blood